Rockabye crocodile - Aruego, Jose.; Dewey, Ariane (New York Greenwillow Books, 1988)
Two elderly boars with contrasting dispositions take turns caring for a baby crocodile and find that their attitudes determine how they are repaid.
Keywords: Pigs -- Fiction; Crocodiles -- Fiction; Behavior -- Fiction